2020
DOI: 10.3390/pharmaceutics12100941
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Co-Amorphous Systems by Freeze-Drying

Abstract: Freeze-drying was evaluated as a production technique for co-amorphous systems of a poorly water-soluble drug. Naproxen was freeze-dried together with arginine and lysine as co-former. To increase the solubility of naproxen in the starting solution, the applicability of five surfactants was investigated, namely sodium dodecyl sulfate, pluronic F-127, polyoxyethylene (40) stearate, tween 20 and TPGS 1000. The influence of the surfactant type, surfactant concentration and total solid content to be freeze-dried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Considerations of bioactivity, structural characteristics of drug and co-former, and physicochemical properties of co-formers on the one hand and consideration of combination therapy on the other hand accounted for 18.1% and 6.8%, respectively. However, a systematic co-former screening was only performed in 21.8% of the reported studies [ 29 , 36 , 41 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Therefore, systematic, predictive, and computational screening methods for co-former selections are still largely unexplored (see also a review: [ 27 ]).…”
Section: Co-former Selection Of Investigated Camsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerations of bioactivity, structural characteristics of drug and co-former, and physicochemical properties of co-formers on the one hand and consideration of combination therapy on the other hand accounted for 18.1% and 6.8%, respectively. However, a systematic co-former screening was only performed in 21.8% of the reported studies [ 29 , 36 , 41 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Therefore, systematic, predictive, and computational screening methods for co-former selections are still largely unexplored (see also a review: [ 27 ]).…”
Section: Co-former Selection Of Investigated Camsmentioning
confidence: 99%
“…Different co-formulated surfactants were investigated with naproxen–arginine and naproxen–lysine CAMS prepared by freeze-drying [ 57 ]. The results indicated that the formulation and the CQA of the CAMS were affected by the type of surfactant.…”
Section: Preparation Of Ternary Camsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many polymeric carriers are hygroscopic, which can lead to API recrystallisation while in some cases polymers can be unsuccessful in maintaining a good stability profile [123]. The applications and limitations of PASDs have been highlighted in a number of reviews [124][125][126]. PASDs incorporate low API loading within a compatible polymer to maintain the solubility advantage of amorphous systems through the formation of strong intermolecular attractions [120].…”
Section: The Design Of Carrier Free Formulations Using Coamorphous Solid Dispersions (Cacds)mentioning
confidence: 99%
“…In addition, many polymeric carriers are hygroscopic, which can lead to API recrystallisation while in some cases polymers can be unsuccessful in maintaining a good stability profile [ 123 ]. The applications and limitations of PASDs have been highlighted in a number of reviews [ 124 , 125 , 126 ].…”
Section: The Design Of Carrier Free Formulations Using Coamorphous Solid Dispersions (Cacds)mentioning
confidence: 99%